Factors Causing the Risk of Diabetes Mellitus in Pregnant Women at The Semanding Community Health Center - Khusnul Maisaroh; Teresia Retna Puspitadewi; Yasin Wahyurianto; Titik Sumiatin (Science Techno Health Journal, 2024)
Introduction : The global maternal mortality ratio has decreased, however this has not yet reached the Sustainable Development Goals (SDG’s) figures. Cases of maternal death in the world are caused by complications during and after pregnancy and childbirth, one of which is gestasional diabetes mellitus. Gestasional diabetes mellitus still often occurs in pregnant women because of certain risk factors that can increase the risk of this condition occuring. Purpose : The aim of this study is to describe the risk factors for diabetes mellitus in pregnant women at The Semanding Community Health Center, Tuban Regency. Method : The research design used descriptive research with a population of 60 pregnant women undergoing examinations from January to March 2024. The sampling technique used is simple random sampling. The research instrument used a questionnaire on risk factors and the incidence of gestasional diabetes mellitus. Results : The results of the study show that almost all pregnant women are at risk of developing gestasional diabetes mellitus with risk factors being that a small number of pregnant women have a history of repeated spontaneous abortions, none of the pregnant women have a history of giving birth to large babies, none of the pregnant women have a history of giving birth to still babies who are not pregnant the cause is clearly known, a small number of pregnant women have a history of pre-eclampsia and eclampsia, none of the pregnant women have a history of polyhydramnios during pregnancy, a small number of pregnant women are over 30 years old, some pregnant women have a history of maternal or family diabetes mellitus, a small number of pregnant women were overweight, none of the pregnant women had a history of recurrent urinary tract infections during pregnancy, a small number of pregnant women had a history of hypertension, and a small number of pregnant women had a history of maternal birth weight above 4000-4500 grams. Discussion : Pregnant women with diabetes mellitus almost never experience clear complaints, so it is important to be examined. Early examination of pregnant women can improve maternal well-being during and after pregnancy.